2023
DOI: 10.1101/2023.03.22.533752
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Basement membrane diversification relies on two competitive secretory routes defined by Rab10 and Rab8 and modulated by dystrophin and the exocyst complex

Abstract: The basement membrane (BM) is an essential structural element of tissues, and its diversification participates in organ morphogenesis. However, the traffic routes associated with BM formation and the mechanistic modulations explaining its diversification are still poorly understood. Drosophila melanogaster follicular epithelium relies on a BM composed of oriented BM fibrils and a more homogenous matrix. Here, we determined the specific molecular identity and cell exit sites of BM protein secretory routes. Firs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
(115 reference statements)
0
2
0
Order By: Relevance
“…Finally, in drosophila, dystrophin is polarized in epithelial migrating cells, where it is found in the posterior half of cells in a complex pattern, illuminating both the cell cortex and filamentous structures partially aligned with F-actin stress fibers 71 . Functional studies have found that the DAPC promotes planar polarization of integrin clusters and participates in the trafficking of ECM components leading to the formation of polarized fibrils 72 .…”
Section: Discussionmentioning
confidence: 98%
“…Finally, in drosophila, dystrophin is polarized in epithelial migrating cells, where it is found in the posterior half of cells in a complex pattern, illuminating both the cell cortex and filamentous structures partially aligned with F-actin stress fibers 71 . Functional studies have found that the DAPC promotes planar polarization of integrin clusters and participates in the trafficking of ECM components leading to the formation of polarized fibrils 72 .…”
Section: Discussionmentioning
confidence: 98%
“…To further validate Dys role in cytokinesis efficiency, we used an optogenetic approach (lightactivated reversible inhibition by assembled trap (LARIAT)) that enables temporally-controlled disruption of protein function by light-induced clustering of endogenously GFP-tagged proteins (Osswald et al, 2022;Qin et al, 2017). To target Dys, we used flies with endogenously sfGFP:tagged Dys, which labels all Dys isoforms (Dennis et al, 2023), and co-expressed GAL4-driven UAS-LARIAT (UAS-VHH:CRY2-P2A-CIBN:MP) in the follicular epithelium (Fig 2D). We first confirmed that blue light exposure of egg chambers cultured ex vivo quickly induces Dys:sfGFP clustering in the basal cortex of follicle cells (Fig 2E).…”
Section: The Dystrophin-associated Protein Complex Promotes Cytokines...mentioning
confidence: 99%